Topical Antibiotic Ointment Versus Silver‐containing Foam Dressing for Second‐degree Burns in Swine. (22nd July 2015) - Toussaint, Jimmy; Chung, Won Taek; Osman, Naureen; McClain, Steve A.; Raut, Vivek; Singer, Adam J.; Zehtabchi, Shahriar
Abstract Objectives Second‐degree burns are very common but their management is controversial. These burns may be treated with either topical antimicrobial agents or advanced occlusive dressings; however, there is no established treatment comparator for preclinical studies. This study was designed to determine which of two commonly used comparator therapies (a silver‐containing advanced dressing or a topical antibiotic ointment) resulted in faster reepithelialization and less scarring. The hypothesis was that second‐degree burns treated with a topical antimicrobial ointment would heal faster and with less scarring than those treated with a silver‐containing occlusive foam dressing in a porcine model. Methods Deep partial‐thickness burns were created on the flanks of three anesthetized female domestic pigs (20 to 25 kg) using a 150‐g aluminum bar preheated in 80°C water bath and applied to the skin for 20 seconds using a force of 2 kg. The burn eschars were excised 48 hours later with an electric dermatome set at a depth of 0.75 mm. The wound beds were treated with a thin layer of triple‐antibiotic petrolatum‐based ointment (changed three times weekly) or a silver‐containing foam dressing (changed once weekly). Full‐thickness punch biopsies were obtained at 9, 11, 14, 16, 18, and 21 days for determination of percentage complete wound reepithelialization and at 28 days for measurement of scar depth. Results At all dressing changes the wounds treated with the topical antibiotic appeared moist, while those treated with the silver‐based dressings appeared dry. At day 21 all wounds treated with the ointment were completely reepithelialized, while only 55% of those treated with the silver dressing were reepithelialized (p < 0.001). Scar depth at day 28 was also significantly less in wounds treated with the topical antibiotic ointment (4.3 mm vs. 5.1 mm, difference = 0.7 mm; 95% confidence interval [CI] = 0.1 to 1.4 mm). There was less scar contraction in wounds treated with the topical antibiotic compared with the silver‐based dressing (mean ± SD = 25.0% ± 14.6% vs. 38.9% ± 16.9%, difference = 13.9%; 95% CI = 5.7% to 22.0%). Conclusions In this model of excised deep partial‐thickness burns, a triple‐antibiotic ointment enhanced reepithelialization and reduced scar depth and contraction compared with a silver‐based foam dressing. This triple‐antibiotic ointment should be considered as a control for studies evaluating novel topical burn therapies.